Proceedings of the Twenty-Fourth Annual ACM-SIAM Symposium on Discrete Algorithms 2013
DOI: 10.1137/1.9781611973105.13
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of detecting taut angle structures on triangulations

Abstract: There are many fundamental algorithmic problems on triangulated 3-manifolds whose complexities are unknown. Here we study the problem of finding a taut angle structure on a 3-manifold triangulation, whose existence has implications for both the geometry and combinatorics of the triangulation. We prove that detecting taut angle structures is NP-complete, but also fixed-parameter tractable in the treewidth of the face pairing graph of the triangulation. These results have deeper implications: the core techniques… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Hardness results are scarce in 3-dimensional computational topology, and to our knowledge all the other difficulty results are deduced from the Agol, Hass, and Thurston construction [1], except for the recent hardness results on computing taut angle structures [4] and optimal Morse matchings [5]. Our result displays a different intractability aspect of this theory.…”
Section: Introductionmentioning
confidence: 76%
“…Hardness results are scarce in 3-dimensional computational topology, and to our knowledge all the other difficulty results are deduced from the Agol, Hass, and Thurston construction [1], except for the recent hardness results on computing taut angle structures [4] and optimal Morse matchings [5]. Our result displays a different intractability aspect of this theory.…”
Section: Introductionmentioning
confidence: 76%
“…To solve this problem, we propose an explicit algorithm for computing maximal alternating cycle-free matchings which is fixed-parameter tractable in the treewidth of this bipartite graph (Theorem 5). Furthermore, we show that finding optimal Morse matchings on triangulated 3-manifolds is also fixed-parameter tractable in the treewidth of the dual graph of the triangulation (Theorem 6), which is a common parameter when working with triangulated 3-manifolds [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, we also show that the W -hierarchy as a purely complexity theoretical tool can be used in a very natural way to answer questions in the field of computational topology. Although there are many results about the computational complexity of topological problems [2,10,19,34,42], to the authors' knowledge, erasability is the first purely geometric problem shown to be W [P ]-complete.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, we propose an explicit algorithm for computing maximal alternating cycle-free matchings which is fixedparameter tractable in the treewidth of this bipartite graph (Theorem 5). Furthermore, we show that finding optimal Morse matchings on triangulated 3-manifolds is also fixedparameter tractable in the treewidth of the dual graph of the triangulation (Theorem 6), which is a common parameter when working with triangulated 3-manifolds [10].…”
Section: Introductionmentioning
confidence: 99%